Association of Selected Physical Fitness Parameters with Club Head Speed and Carry Distance in Recreational Golf Players. Issue 4 (December 2013) - Loock, Henriette; Grace, Jeanne; Semple, Stuart
The purpose of this study was to determine the association between selected physical fitness parameters and club head speed (CHS) as well as carry distance (CD) in recreational golf players. The study population comprised 101 male recreational golf players (age: 38.23 +/– 16.55 y). Using the driver and iron, both CHS and CD were measured utilising Flightscope technology. Lower back flexibility (sit-and-reach), muscle resistance/endurance (sit-ups, push-ups and wall-squats), muscle resistance (back dynamometer), cardio respiratory fitness (3 minute step-test) and balance (Biodex Balance System) were also measured for each participant. A positive association was observed between lower back strength and driver CD (r = 0.470), driver CHS (r = 0.558), iron CD (r = 0.439) and iron CHS (r = 0.597). Weaker associations were observed between push-ups and driver CHS (r = 0.285) as well as wall-squats and driver CHS (r = 0.250). When compared with other physical fitness parameters in recreational golf players, lower back strength seems to account for more of the variance observed in CHS and CD. These observations tend to suggest that lower back strength is an important contributor towards the execution of the golf swing and as such should be addressed through appropriate resistance and conditioning interventions.